2021
DOI: 10.21203/rs.3.rs-963590/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conventional GnRH Antagonist Protocols Versus GnRH Agonist Long Protocol on IVF/ICSI Outcomes in Women With Polycystic Ovary Syndrome: A Systematic Review and Meta- Analysis of Randomized Controlled Trials

Abstract: BackgroundGonadotropin-releasing hormone (GnRH) analogues are commonly used in clinical practice to prevent premature luteinizing hormone (LH) surge during In-Vitro Fertilization/ Intra-Cytoplasmic Sperm Injection (IVF/ICSI) cycles. This review aimed to summarize the available evidence comparing the effects of conventional GnRH antagonist protocols, the most commonly used GnRH antagonist protocols, and GnRH agonist protocols on IVF/ICSI outcomes in women with polycystic ovary syndrome (PCOS). MethodsA comprehe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 85 publications
(206 reference statements)
0
2
0
Order By: Relevance
“…Nevertheless, unlike stimulation duration, the effects on gonadotropins consumption and the number of retrieved oocytes were insigni cant. However, based on our recent systematic review and meta-analysis on PCOS women [77], using conventional GnRH antagonist protocols led to a signi cantly lower gonadotropin consumption and a signi cantly lower number of retrieved oocytes compared to the long agonist one. (Gonadotropin consumption; WMD= -221.36, 95% CI: [-332.28 to -110.45] IUs; P < 0.0001; I 2 = 43%; χ ² -P = 0.1; high-quality evidence), (number of retrieved oocytes; WMD = 1.82, 95% CI: [-3.48 to -0.15] oocytes; P = 0.03; I2 = 58%; χ² P = 0.02; low-quality evidence), Thus, the insigni cant result may relate to the relatively low sample size of the current trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, unlike stimulation duration, the effects on gonadotropins consumption and the number of retrieved oocytes were insigni cant. However, based on our recent systematic review and meta-analysis on PCOS women [77], using conventional GnRH antagonist protocols led to a signi cantly lower gonadotropin consumption and a signi cantly lower number of retrieved oocytes compared to the long agonist one. (Gonadotropin consumption; WMD= -221.36, 95% CI: [-332.28 to -110.45] IUs; P < 0.0001; I 2 = 43%; χ ² -P = 0.1; high-quality evidence), (number of retrieved oocytes; WMD = 1.82, 95% CI: [-3.48 to -0.15] oocytes; P = 0.03; I2 = 58%; χ² P = 0.02; low-quality evidence), Thus, the insigni cant result may relate to the relatively low sample size of the current trial.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the differences in the consumed dose of gonadotropins and the divergent effects of GnRH analogues on steroidogenesis may affect the regulation of ovarian Moreover, FSH induces the expression of transforming growth factor-β (TGF-β) [91], which also controls VEGF expression and acts synergically with HIF-1α in upregulating VEGF expression [92]. Above that, Based on our recent systematic review and meta-analysis [77], treating PCOS women with the conventional GnRH antagonist protocols led to lower levels of estradiol on hCG day compared to the standard long agonist protocol (WMD= -259.21, 95% CI: [-485.81 to -32.60] pg/ml; P = 0.02; I 2 = 42%; χ ² -P = 0.10; moderate-quality evidence), which agrees with the previous in vitro studies that demonstrated lower aromatase activity and expression from granulosa lutein cells of GnRH antagonist-treated women compared to those of GnRH agonist-treated women [93]. Estrogen upregulates VEGF expression in ovarian [94] and endometrial cells [95,96].…”
Section: Discussionmentioning
confidence: 99%